Calcium phosphate biocement using bone meal and acid urease: An eco-friendly approach for soil improvement - Gowthaman, S.; Yamamoto, M.; Nakashima, K.; Ivanov, V.; Kawasaki, S. (Elsevier, 2021)
Biocementation technology has recently become a new soil improvement method. In majority of the bio cementation processes, the formation of calcium carbonate occurs as the consequence of enzymatic urea hy drolysis, producing carbonate-ions and alkaline pH (ranging between 8.5–9.5). The problem of conventional biocementation method at alkaline conditions is the release of ammonium ions (that pollute water) and gaseous ammonia (that pollutes atmosphere). In this paper, a new biocementation method is proposed, which involves calcium phosphate precipitation driven by enzymatic hydrolysis of urea. The bone meal, one of the potential and low-cost sources of calcium phosphate, was acid-dissolved and injected into the sand altogether with urea and acid urease. Due to the enzymatic hydrolysis of urea, the pH of the reaction medium increased, hence the calcium phosphate was tended to precipitate within the pores and bind the soil particles. The content of urea was varied in biocement solution to control the increase of pH during reaction, thus the biocementation was in different pH ranges. The precipitated calcium phosphate compound was found to be brushite, but its morphology highly varied depending on the pH conditions. Molar calcium/urea ratio of 1.5 in calcium phosphate biocementation solution resulted in preferrable formation of plate-like crystals within the sand matrix and increased unconfined compressive strength up to 1.5 MPa. Meanwhile, the conventional biocementation is performed at molar cal cium/urea ratio from 0.66 to 1.0. The calcium phosphate biocementation at pH changing from 3.4 to 7.5 indicated the potential decrease of ammonium ions release to environment by about 50% and the emission of toxic gaseous ammonia by approximately 90% in comparison with conventional biocementation.
Keywords: Biocementation; Calcium phosphate; Bone meal; Urea hydrolysis; Acid urease